Innovation in High Reliability Ambidextrous Organizations Analytical Solutions Toward Increasing Innovative Activity - Kraner, Jan (Contributions to Management Science, 2018)
Companies need to invest in innovation in order to ensure their long-term survival. This book focuses on how and why key players support or obstruct the implementation of a technological innovation in ambidextrous organizations, and how the interaction between players involved in daily business and innovation affects implementation of innovation in 'high reliability organizations'. This book argues that an organization has to create new innovations or adopt innovations to constantly deliver attractive products on the one hand, while also adjusting and improving current products and processes on the other. In turn, it addresses a specific problem: What if a company operates in an innovation-averse and procedural environment and culture? Drawing on case studies, focus group studies and a unique analytical framework, it then provides ways for companies to overcome this situation.